Special interest tourismforsmall scale industry development of the north central province of sri lanka - NishanthaHettiarachchi, H.A. (university of Jaffna, 2014)
Special interest tourism, one of the latest touristic trends of the mass tourism industry, focuses the sustainable form of tourism and is steadily attracting worldwide interest. It has emerged as an alternative to the large scale tourism development that has led to environmental, cultural and societal degradation. Over the last few decades, it has provided numerous opportunities to enhance and promote the small scale industries in the peripheral regions of the third world countries. The main objective of this study is to analysis the present and potential contribution of special interest tourism on the development of small scale industries of the North Central Province (NCP) of Sri Lanka.Further, attention is given to identify the role of tourism related small scale industries on the development of the region. The methodology of this study comprises a number of steps; a) preliminary survey to select the study area, b) pilot survey to test questionnaires, c) data collection and d) data analysis.After a preliminary survey Anuradhapura historic city, Mihintale and Tantirimale sacred cities of the NCP were selected for the study. Twenty nine villages of the region, where special tourism activities can be seenwere selected as the study area. A thirty percent sample from each village, hundred tourists both domestic and foreign and thirty owners of tourist hotels were selected for the in-depth study. Both quantitative and qualitative analytical methods were used in combination for analysis the collected data. The overall findings of this study are that, special interest tourism of the region has contributed to the development, promotion and enhancement of small scale industries generating income and employment opportunities to the host communities and agricultural and livelihood development of the NCP while ensuring the regional development process of the region. As this study explores the role of special interest tourism in developing small scale industries of the region, it can contribute to policy formulation for promoting tourism related economic activities and regional development strategies of Sri Lanka.
Keywords: Special interest tourism; Small scale industries; Regional development